Family Acupuncture Medicine and Acupuncture Clinic Management - NAKAZAWA, Ryohei (Zen Nihon Shinkyu Gakkai zasshi (Journal of the Japan Society of Acupuncture and Moxibustion), 2024)
Herein, acupuncture medicine that incorporates the knowledge of family medicine will be referred to as "family acupuncture medicine". Acupuncture clinic management requires a balance between treatment philosophy and management philosophy, and knowledge of family medicine is useful with regard to an "academic field for research into human aspects", which learning is a requisite for management.Family medicine is comprised of three aspects, those being "patient-centered medicine", "family-oriented care", and "community-based primary care", with this definition being the same as primary care. In order to manage an acupuncture clinic that will be of use in the community, it is necessary to learn not only treatment-related technology but also family medicine, and to practice community based primary care using patient-centered medicine methods, family-oriented care, and community outreach.The continuing decrease in the population of Japan means that there is little leeway in the national budget, and it is believed that there will be a demand for acupuncture clinics that practice family medicine focused on preventative measures.